2015
DOI: 10.1177/2329496515620646
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Sociological Research through Public Records Requests

Abstract: Sociologists rarely attempt to obtain public records through freedom of information requests (FOIR), despite the numerous ways such requests can contribute to social research. FOIR refers to the process of procuring data from the government through public records laws and requests. The limited sociological literature on FOIR largely portrays it as a critical-activist tool that requires an uncertain and time-consuming process. But these conceptions vastly limit the scope and usefulness of FOIR as a data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…I discuss my experience using FOI requests on Ontario universities and elaborate on lessons learned along the way. As many scholars have argued, it is important for researchers to document the ATI/FOI process and to outline and reflect on the obstacles and barriers they encounter in their attempts to obtain access to the backstage of institutional practice (Luscombe and Walby 2017, 384; Greenberg 2016, 110; Monaghan 2015, 53). Given that ATI/FOI training is still for the most part not included in graduate programs in social science disciplines, empirical accounts of ATI/FOI in action offer researchers an invaluable resource for enhancing their understanding of the mechanics and limitations of the brokering process.…”
Section: Researching Higher Education Using Access To Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…I discuss my experience using FOI requests on Ontario universities and elaborate on lessons learned along the way. As many scholars have argued, it is important for researchers to document the ATI/FOI process and to outline and reflect on the obstacles and barriers they encounter in their attempts to obtain access to the backstage of institutional practice (Luscombe and Walby 2017, 384; Greenberg 2016, 110; Monaghan 2015, 53). Given that ATI/FOI training is still for the most part not included in graduate programs in social science disciplines, empirical accounts of ATI/FOI in action offer researchers an invaluable resource for enhancing their understanding of the mechanics and limitations of the brokering process.…”
Section: Researching Higher Education Using Access To Informationmentioning
confidence: 99%
“…An impressive multi-disciplinary and international social science literature has emerged based on the analysis of ATI/FOI disclosures. Critical scholars have mobilized ATI/FOI requests in research on policing, security, and carceral organizations in Canada (Wright, Moore, and Kazmiersky 2015; Luscombe and Walby 2015; Rigakos and Worth 2011; Kinsman and Gentile 2010; Piché 2011; Piché and Walby 2010; Yeager 2008; see also Brockman 2018), Britain (Rappert 2012; Brown 2009), and the United States (Greenberg 2016; Lee 2001). While this body of literature has demonstrated that ATI/FOI requests can be used to good effect in facilitating access to information about the activities of government agencies, it has also highlighted important gaps between the official promise of ATI/FOI law and the reality of access barriers and continued organizational secrecy and obfuscation.…”
Section: Introductionmentioning
confidence: 99%
“…To address such limits, Savage and Hyde suggest that ATI/FOI requests should be combined with other research methods, most of which are easily complemented by ATI/FOI. What makes ATI/FOI such a unique and worthy means of producing data is that the records disclosed document trends in government deliberations and decision-making (Greenberg, 2016; Gingras, 2012; Jiwani and Krawchenko, 2014; Keen, 1992; Lee, 2005; Savage and Hyde, 2013; Walby and Larsen, 2012), and as such these disclosures are not subject to the same rhetorical flashes and impression management that political speeches and media releases are.…”
Section: Existing Literature On Freedom Of Information Requests In Somentioning
confidence: 99%
“…First, there is literature based on analysis of disclosures, usually in sociology, legal studies, history, criminology and criminal justice, and political science (e.g. Greenberg, 2016; Jiwani and Krawchenko, 2014; Keen, 1999; Savage and Hyde, 2014). In Canada, for example, there is literature on policing, national security, corporate security, post-secondary education, and other topics that uses ATI/FOI as a primary data source (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The MSHA data set included geographic coordinates for each 6 There are numerous limitations to cross-sectional work, including the possibility of omitted variable bias-when a model leaves out an important variable that may influence the observed relationship (Gordon 2010). 7 I expound on the details of the data collection method used in this study elsewhere (Greenberg 2016). impoundment. However, the MSHA data was only current for 2013, so I had to determine which impoundments were active in 2000 in order to match the time frame of the census data.…”
Section: Dependent Variablementioning
confidence: 99%